Last girl ghosted ebook A novel. - Unger, Lisa (2021)
"A five-alarm fire of a situation...the surprises keep coming." —The New York Times Secrets, obsession and vengeance converge in this riveting thriller about an online dating match turned deadly cat-and-mouse game, from the New York Times bestselling author of Confessions on the 7:45 She met him through a dating app. An intriguing picture on a screen, a date at a downtown bar. What she thought might be just a quick hookup quickly became much more. She fell for him—hard. It happens sometimes, a powerful connection with a perfect stranger takes you by surprise. Could it be love? But then, just as things were getting real, he stood her up. Then he disappeared—profiles deleted, phone disconnected. She was ghosted. Maybe it was her fault. She shared too much, too fast. But isn't that always what women think—that they're the ones to blame? Soon she learns there were others. Girls who thought they were in love. Girls who later went missing. She had been looking for a connection, but now she's looking for answers. Chasing a digital trail into his dark past—and hers—she finds herself on a dangerous hunt. And she's not sure whether she's the predator—or the prey. Don't miss The New Couple in 5B , Lisa Unger's newest psychological thriller about a couple that inherits an apartment with a truly chilling past. Looking for more spine-tingling thrillers? Check out these other titles by New York Times bestselling author Lisa Unger: Under My Skin The Stranger Inside Confessions on the 7:45 Secluded Cabin Sleeps Six The New Couple in 5B (coming March 2024!)